TUC Union Yes campaign, 1990 (London, 1990)
1990 1980-95 "TUC Union Yes campaign, 1990" [BW0143], 1990, Trades Union Congress The Manchester Evening News for March 5, 1990 gives front page publicity to the TUC Union Yes campaign to promote trade union organisation and recruitment in Greater Manchester.